Pengaruh Pemberian Pakan Daphnia yang Diperkaya Vitamin C Terhadap Pertumbuhan dan Sintasan Larva Ikan Nilem Osteochilus vittatus - Hendriana, Andri; Maynanda, Rebecca; Eny Indriastuti, Cecilia; Iskandar, Andri; Tri Wahyudi, Imam; Maruto Darmawangsa, Giri (JARI : Jurnal Akuakultur Rawa Indonesia, 2025)
Nilem fish Osteochilus vittatus is an economically valuable freshwater species that also supports ecological sustainability. However, its aquaculture is hindered by slow larval growth and high mortality rates. This study aimed to evaluate the effectiveness of vitamin C-enriched daphnia as a dietary supplement to enhance the growth performance and survival of nilem fish larvae. A Completely Randomized Design (CRD) was implemented, consisting of 4 treatments with 3 replicates each: VC0 (0 mg L-¹), VC200 (200 mg L-¹), VC250 (250 mg L-¹), and VC300 (300 mg L-¹) of vitamin C enrichment. Larvae aged 15 days were stocked at a density of 5 individuals L-1 in aquarium containing 7 L of water. Enrichment was conducted by immersing daphnia in vitamin C solutions for 3 hours prior to feeding. The results indicated that vitamin C supplementation significantly improved larval growth (p<0.05), with the highest length and weight gains observed in treatments VC300. However, survival rates peaked at 100% in VC200 and VC250 treatments. The study concludes that vitamin C-enriched daphnia, particularly at 200–250 mg L-¹, effectively enhances both growth and survival in nilem fish larvae